Предмет: Алгебра,
автор: Tyrbo3235
4x^-(x-3y)^ помагите пожалуста
Ответы
Автор ответа:
0
4x^2-(x-3y)^2=
=(2x-(x-3y))*(2x+x-3y)=
=(2x-x+3y)*(3x-3y)=
=(x+3y)*3(x-y)
Или же можно упростить:
4x^2-(x-3y)^2=
=4x^2-(x^2-6xy+9y^2)=
=4x^2-x^2+6xy-9y^2=
=3x^2+6xy-9y^2.
=(2x-(x-3y))*(2x+x-3y)=
=(2x-x+3y)*(3x-3y)=
=(x+3y)*3(x-y)
Или же можно упростить:
4x^2-(x-3y)^2=
=4x^2-(x^2-6xy+9y^2)=
=4x^2-x^2+6xy-9y^2=
=3x^2+6xy-9y^2.
Автор ответа:
0
4x²-(x-3y)²=(2x-(x-3y))(2x+x-3y)=(2x-x+3y)(3x-3y)=(x+3y)(x-y)*3
Похожие вопросы
Предмет: Русский язык,
автор: sabrinakardanova364
Предмет: Математика,
автор: MILASHKAA19
Предмет: Математика,
автор: qirina78
Предмет: Математика,
автор: Аноним